PIPER ATIVIDADES FILM SEMIOTICS ANALYSIS (LITTLE BIRD BABY WIN OSCAR) - NISA AMANDA; Mahendra Mahendra; Anggi Widiarti; Siti Kartika Dewi (Universitas Pendidikan Indonesia, 2021)
“Piper is a beautiful character,” said Barillaro. Reporting from Business Insider, Piper was inspired by a collection of Sandpiper birds on a beach close to the Pixar studio in Emeryville, California. “Piper” is a short animated film from Pixar that was screened before the film “Finding Dory” on June 17, 2016. With a duration of 6 minutes, “Piper” tells the story of a baby Sandpiper bird who is learning how to look for shells on the beach. He was traumatized by being rolled up by the waves. But finally he found how he got more shells than other birds. The film, directed by Alan Barillaro, won an Oscar 2017. This research finds signs and signs as the main elements in semiotics are present in every scene of the film. The placement of signs and markers is considered appropriately in order to show the message desired by the film.